Coagulopathy secondary to chicken pox: a case report - Kaur, Harharpreet; Mohan, Gurinder; Singh, Harsehaj; Singh, Gurraj; ., Anusha (International Journal of Advances in Medicine, 2017)
Chickenpox often produces a self-limiting disease in children and adolescents. The clinical course is usually mild and complications are rare. The complications that are known to be associated with it are pneumonia, meningitis, myocarditis and nephritis. Severe and disseminated varicella infection with organ dysfunction can also be seen amongst diabetics and immunocompromised patients. However, it is not commonly known that varicella can be life threatening even in immunocompetent adult patients. We present a case of a healthy adult male in which this infection progressed to malignant hemorrhagic disease associated with coagulopathy.